2010
DOI: 10.1038/oby.2010.34
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Free‐Living Energy Expenditure Using a Novel Activity Monitor Designed to Minimize Obtrusiveness

Abstract: The aim of this study was to investigate the ability of a novel activity monitor designed to be minimally obtrusive in predicting free‐living energy expenditure. Subjects were 18 men and 12 women (age: 41 ± 11 years, BMI: 24.4 ± 3 kg/m2). The habitual physical activity was monitored for 14 days using a DirectLife triaxial accelerometer for movement registration (TracmorD) (Philips New Wellness Solutions, Lifestyle Incubator, the Netherlands). TracmorD output was expressed as activity counts per day (Cnts/d). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 29 publications
5
100
1
Order By: Relevance
“…PA patterns were determined using a PA monitor-the DirectLife triaxial accelerometer for movement registration (TracmorD) (Philips Consumer Lifestyle, the Netherlands; Bonomi et al 2010;Plasqui et al 2005;Plasqui and Westerterp 2007)-and a self-reported Baecke PA questionnaire (Baecke et al 1982) which was completed online. The accelerometer-based monitor (Philips DirectLife Activity Monitor, the Netherlands) was posted to each participant.…”
Section: Physical Activitymentioning
confidence: 99%
“…PA patterns were determined using a PA monitor-the DirectLife triaxial accelerometer for movement registration (TracmorD) (Philips Consumer Lifestyle, the Netherlands; Bonomi et al 2010;Plasqui et al 2005;Plasqui and Westerterp 2007)-and a self-reported Baecke PA questionnaire (Baecke et al 1982) which was completed online. The accelerometer-based monitor (Philips DirectLife Activity Monitor, the Netherlands) was posted to each participant.…”
Section: Physical Activitymentioning
confidence: 99%
“…Tracmor D (Philips New Wellness Solutions, Lifestyle Incubator) provides visual feedback to the activity monitor user in terms of percentage of activity performed as compared with a specific target established in the intervention program. 66 This would increase the ability of the user to act in response to the indication of an inadequate activity level.…”
Section: Physical Activity and Health Promotionmentioning
confidence: 99%
“…64,65 A more recent version of this accelerometer, the DirectLife tri-axial accelerometer for movement registration (Tracmor D; Philips New Wellness Solutions, Lifestyle Incubator), showed similar prediction accuracy of energy expenditure in free-living conditions. 66 The activity counts measured with Tracmor D (Philips New Wellness Solutions, Lifestyle Incubator) added 23% to the explained variation in AEE after adjustment for subject characteristics, and the prediction model had a standard error of estimation of 0.9 MJ day À1 . Although significant estimations of AEE have been shown with an accelerometer, there are pragmatic limitations to the use of activity counts to estimate energy expenditure.…”
Section: Activity Energy Expenditure Estimation Using Accelerometersmentioning
confidence: 99%
“…For instance, a triaxial accelerometer, Tracmor, has yielded promising results in adults (9) and in a group of 3-to 4-year-old children (6) . However, this device is currently not commercially available for use in young children.…”
Section: Introductionmentioning
confidence: 99%